SLANGS IN BEYONCE KNOWLES’ SONGS - Christina Septiani Manurung and Elia Masa Gintings (LINGUISTICA, 2015)
This study is based on sociolinguistics problems. It deals with the use of slang.The writer focuses on Beyonce Knowles’s songs lyrics as the scope of data. Theobjectives of the study were to find out the types of slang are used in BeyonceKnowles’ songs and to reason for the use of the types of slang in BeyonceKnowles’ songs. The data that support this study by using descriptive qualitativedata by reading some references related to the subject matters. The findingsshowed Abbreviation and Baby’s Expression slang were found in each lyrics ofBeyonce Knowles songs. There weren’t found Grammatical slang in two songslyrics among ten songs, nor the Words Repetition, there weren’t found in foursongs lyrics. The writer concluded that Abbreviation is the most dominant type ofslang found in Beyonce Knowles’ songs.